Mechanical Properties of Compression Molded Epoxy Polymer Composites Reinforced with Kenaf Fibers / Nur Farhani Ismail ...[et al.] - Ismail, Nur Farhani; Muhamad, Norhamidi; Sulong, Abu Bakar; Che Haron, Che Hassan; Tholibon, Dulina; Tharazi, Izdihar; MdRadzi, Mohd Khairul Fadzly; Razak, Zakaria (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Kenaf composites have been widely used in the engineering and industrial applications such as air cleaner, dashboard, insulation mats, and fibreboard. Due to considerable attentions; kenaf fibres are reinforced in polymers for the fabrication of polymer composites. This work deals with the fabrication and characterizations of untreated and treated temafa kenaf fibres. The microstructure (SEM), flexural properties and tensile properties of the prepared kenaf polymer composites were discussed throughout this study. The kenaf fibres were treated with 6 wt% sodium hydroxide, NaOH solution for 24 hours soaking time. The epoxy thermoset reinforced with randomly oriented temafa kenaf was fabricated using compression molding technique. The composite samples of kenaf were prepared with different kenaf fibre loadings; 20 wt%, 30 wt%, 40 wt%, 50 wt% and 60 wt% . It was found that the properties of kenaf composites mainly depend on the compositions of kenaf fibres. It has also been investigated that the treatment influences the properties of kenaf itself. Overall, the results revealed that the treated kenaf composites have better mechanical properties such as flexural strength as compared to the untreated kenaf composites. However, it is observed that the flexural strength also increased with increasing percentage loading of kenaf fibres. These prepared kenaf composites will perform better mechanical properties than existing polymer may be used in automotive applications.